Ethical issues using artificial intelligence in healthcare - Lemonnier, Noemi (2021)
This thesis presents the results of the Systematic Mapping Study of Artificial Intelligence (AI) Ethics in healthcare. AI ethics thrives to reduce ethical issues to create moral, fair, and safe AI applications. This thesis aims to provide a more precise view of AI ethics in healthcare. In healthcare, the four main ethical issues mentioned throughout various published research are transparency, justice and fairness, accountability and responsibility, and privacy and security. As the AI industry is constantly expanding, AI ethics in healthcare will become a growing concern for society. Additionally, the AI field can lack information, clarity, and structure. Thus, identifying the origin of ethical issues and providing solutions for them will be relevant for the day-to-day and academic spheres. A clear proposition to lessen these ethical issues in the research domain has yet to be mentioned as most research focus on highlighting issues without providing concrete solutions. This thesis contributes to the research field by analyzing the relationships between the different stakeholders involved and their respective ethical issues. A total of 56 papers were analyzed and the results were 15 empirical conclusions that highlighted the current literature and its gaps, for example, which stakeholder is mentioned less and research more to limit further moral issues.